SOLUSI MASALAH TRANSPORTASI MENGGUNAKAN TOCM-SUM APPROACH DENGAN INDIKATOR DISTRIBUSI - Astuti, Nita Dwi; Utomo, Robertus Heri Soelistyo; Djuwandi, Djuwandi (MATEMATIKA, 2016)
Transportation problems are related to the transport of a product from some sources to a number of different destination. In general, the different delivery will produce different shipping cost, therefore the purpose of solving classic transportation problems with the allocation of delivery from the source to destination is to determine the minimum transportation costs. The appropriate allocating in each case will produce an optimal solution for both minimize case and maximize case. TOCM-SUM approach with the indicator distribution is a new method for seeking initial feasible solution of the transportation problem. This method was proposed by Aminur Rahman Khan, Adrian Vilcu, MD.Sharif Uddin and FlorinaUngureanu. The first step is create a table of transportation, the second step is reduce the elements in each row and column with the smallest elements in every row and column, the third case is form the tables of Total Opportunity Cost Matrix (TOCM), the fourth case is calculate the indicators of distribution of each row and column in the TOCM table, and thereafter, the allocation is given to the cell that has the minimum distribution indicator. Repeat the steps until the total allocation of supply and demand is met, for optimal solutions the method of Stepping Stone is being used. This article discusses the application of TOCM-SUM Approach with the indicator distribution – Stepping Stone in the CV. Tirta Makmur Ungaran.